PENGARUH PENGETAHUAN KORUPSI TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN PATRIOTISME SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA UMKM DI KABUPATEN BANTUL) - Dewi Kusuma Wardani,; Vina Bella Rosita , (Journal of Innovation Research and Knowledge, 2022)
This study aims to determine whether knowledge of corruption affects the mandatory compliance of SMEs with patriotism as a moderating variable. This research is quantitative data. This study uses primary data with the sampling method convenience sampling. The sample taken in this study was 100 respondents from micro, small and medium enterprises in Bantul district. The data analysis technique uses path analysis with knowledge of corruption as the independent variable, SMEs taxpayer compliance as the dependent variable, and patriotism as the moderating variable. The results of the analysis conclude that knowledge of corruption does not affect the compliance of U SMEs taxpayers as evidenced by the T-statistic value of 0.145 (> 1.96) and the original sample value is negative 0.313 and patriotism cannot strengthen the relationship of knowledge of corruption to SMEs taxpayer compliance as evidenced by the value of T-statistic is 0.532(>1.96), P-value is 0.595(>0.05) and the original sample estimate is negative 0.021.